Akurasi dimensi produk filamen 3d printing berbahan polipropilen menggunakan mesin ekstrusi - Mochamad Edoward Ramadhan; Mahros Darsin; Sains Ilham Akbar; Danang Yudistiro (Jurnal Teknosains, 2022)
Additive manufacturing (AM) has been trending topic in industrial revolution 4.0. One technique and the most widely used AM is fused deposition modeling (FDM), which uses a melted filament and deposited it layer by layer. The common filaments used are made of PLA, PP, and ABS, which are available at the online market with variety of prices depend on the quality. It is an advantage if we can make these filaments. In filament manufacturing, the dimensional accuracy is one of the most important factors to comply with the existing 3D printers. The aim of this research is to fabricate a filament made of PP, then assessed the quality based on the accuaray of the targeted diameter of 1.75 mm. The manufacturing process used a self-made plastic extrusion machine. Variations were made on three variables with three levels each. There are (i) heater band temperature with a minimum and maximum range (150/170 oC, 155/175 oC and 160/180 oC), (ii) winding speed (13 mm/s, 16 mm/,s and 19 mm/s), and (iii) roll distance to the nozzle set point (200 mm, 500 mm and 700 mm). Taguchi L9 design was used to design the experiments and analysis.Minitab 19 was employed to find the S/N ratio and analysis the variance (ANOVA). The results of the analysis state that two parameters have a significant effect on the dimensions of the filament, i.e. temperature and roll distance to the nozzle, while, the winding speed has no dominat effect. The best accuracy of filaments diameter was achieved when applying a combination of temperature (160/180 ⁰C), the distance between the nozzle to the roll of 700 mm, and winding speed of 13 mm/s.